OPTIMALISASI WAKAF DI INDONESIA - choirunnisak, choirunnisak (Institut Agama Islam Bengkulu, 2019)
This study aims to find out how to optimize waqf in Indonesia specifically to improve the economy in Indonesia. This research is a libraty research which focuses on qualitative data management with data analysis methods using descriptive analysis methods. The results of this study are seven things that must be done, namely: (1). Carry out a thought approach based on the study of the school of fiqh which is mostly used by Indonesian Muslim communities. (2). Provide socialization regarding the importance of empowering waqf more productively for the acceleration of development of Indonesia. (3) giving an overview and simulation of the benefits and benefits to be obtained by managing waqf productively. (4) Encouraging the creation of qualified HR waqf managers. (5). Encourage the habitual creation of alternative and investment climate that is optimal for the utilization of waqf. (6). Synergize with all related parties. (7) Optimizing the role of the Indonesian Waqf Agency.